Grammatical inclusion in Diwan Al-Hamasa by Abu Tammam: An Applied Study - Alsawadheh, Ahmad Abdelsalam Saleh (Journal of Humanities & Social Sciences, 2020)
This research aims at studying the phenomena of (grammar implication) in (Hamasah collection of poems) and it includes the various ideas that appeared in various references. For example; interpretation of Quran، Arabic Grammar and rhetoric aiming at observing this phenomenon in order to be applied on this collection of poems and its essence to reach the implication borders based on the scientific study of this collection of poems.